2018
DOI: 10.1111/plb.12844
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intraspecific seed diversity in Astragalus aquilanus (Fabaceae), an endemic species of Central Apennine

Abstract: This work aims to study seeds of the endemic species Astragalus aquilanus from four different populations of central Italy. We investigated seed morpho-colorimetric features (shape and size) and chemical differences (through infrared spectroscopy) among populations and between dark and light seeds. Seed morpho-colorimetric quantitative variables, describing shape, size and colour traits, were measured using image analysis techniques. Fourier transform infrared (FT-IR) spectroscopy was used to attempt seed chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
1
3
0
2
Order By: Relevance
“…se analizaron, se confirman los beneficios referidos respecto a la confiabilidad y rapidez de la metodología digital, indicados en otras investigaciones (Varga et al 2019;Di Cecco et al 2019).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…se analizaron, se confirman los beneficios referidos respecto a la confiabilidad y rapidez de la metodología digital, indicados en otras investigaciones (Varga et al 2019;Di Cecco et al 2019).…”
Section: Resultados Y Discusiónunclassified
“…Para Duc et al (2015), esta variable junto a los valores de longitud, son considerados como descriptores relevantes para la especie, lo que permite captar información de la diversidad genética entre accesiones. También, pueden ser utilizados como indicadores de selección en el mejoramiento genético, por su relación con el rendimiento en campo (Yildiz et al 2016;Di Cecco et al 2019;Alharbi & Adhikari, 2020). A partir de los valores morfológicos, las variedades Beso de novia, Argentina y Rosada fueron catalogadas como pequeñas; las variedades Semiverde, Roja y Blanca común, se agruparon con tamaño medio y la variedad Alpargata fue definida como un material de semillas grandes (Tabla 3).…”
Section: Parámetrounclassified
“…Based on an analysis of the intraspecific plasticity exhibited in morphology, colour and chemical composition of seeds of four populations of Astragalus aquilanus , Di Cecco et al . () also concluded that climate variables strongly affect the type of seed produced. In contrast, a variation in environment associated with an altitudinal span of 1000 m had little effect on the germination of Helichrysum microphyllum , where all seed lots were non‐dormant (Picciau et al .…”
Section: Changing Environmental Effectsmentioning
confidence: 96%
“…Di Cecco et al . () used image analysis techniques to quantify morpho‐colorimetric variables and describe shape, size and colour; and used Fourier‐transform infrared (FTIR) spectroscopy for the chemical characterisation of the seeds. Similarly, seeds of Lathyrus linifolius were characterised using physical, colorimetric and chemical techniques (Dello Jacovo et al .…”
Section: Technical Advancesmentioning
confidence: 99%
“…In the present work, attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy in the mid-range (4000-400 cm −1 ) was utilized to attempt a discrimination of autochthone potato accessions cultivated in the mountain territory of Majella National Park (Abruzzo, Italy) and commercial varieties usually grown in the same area. Apart from the safeguard of natural biodiversity and the wilderness, many actions are currently being implemented in the Majella National Park to valorize the local germplasm [35,36] and promote the sustainable economic development of rural areas. In this context, the plant genetic resources of the Majella National Park, including potatoes, have been recently rediscovered.…”
Section: Introductionmentioning
confidence: 99%